Expanding Promotion and Marketing of Village Products Through Smart Village System - Muhammad Raihan; Edi Surya Negara (LPPM Universitas Islam 45 Bekasi, 2023)
Several villages in South Sumatra do not yet have a way to develop and advance their economy by selling local products that they make themselves, one of which is Burai Village. These products consist of agricultural products, handicrafts, special foods and typical clothing from the village. So far, the products they make are only sold and bought by people close to the village, both people from within the village and from outside the village. That way the income of village product sellers is not that big because the products they sell don't have a place to promote their products so that they can be known by many people and can be disseminated. To promote these village products, the author will make a Village Product catalog on the Sistem Desa Pintar (SIDESPIN) website, using the Web Engineering method and the Laravel framework to make it easier to develop the village product catalog features. With this research a village product catalog will be produced on the SIDESPIN website such as e-commerce which will be used to promote the village's products so that they can be known more widely.